2007
DOI: 10.1016/j.jneuroim.2007.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Myelin oligodendrocyte glycoprotein peptide-induced experimental allergic encephalomyelitis and T cell responses are unaffected by immunoproteasome deficiency

Abstract: The inoculation of MOG peptides into C57BL/6 mice induces CD4 + and CD8 + T cells, and recent work has shown that adoptive transfer of the latter population, after extensive in vitro stimulation, can cause EAE in naïve recipient mice. Herein, we have evaluated the incidence and severity of EAE, and the induction of CD4 + and CD8 + T cells, following MOG peptide inoculation of wt mice and of LMP-2KO mice that lack an intact immunoproteasome, a cytoplasmic organelle that is induced by chronic inflammation and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 73 publications
4
17
0
1
Order By: Relevance
“…No significant difference in disease scores was observed between LMP7 −/− and wild-type mice (Figure 5), in clear contrast to the results reported by Seifert et al. (2010) but consistent with the study by Frausto et al. (2007), who found no effect of LMP2 deficiency on the course of EAE.…”
Section: Resultssupporting
confidence: 92%
“…No significant difference in disease scores was observed between LMP7 −/− and wild-type mice (Figure 5), in clear contrast to the results reported by Seifert et al. (2010) but consistent with the study by Frausto et al. (2007), who found no effect of LMP2 deficiency on the course of EAE.…”
Section: Resultssupporting
confidence: 92%
“…Interestingly, we found that mice genetically deficient in any of the immunoproteasome active site subunits developed EAE following MOG 35–55 immunization that was indistinguishable from wild type C57BL/6 mice (Fig ). Similar results using LMP2 −/− mice have been reported by Frausto et al () while Seifert et al have reported that MOG 35–55 immunization of LMP7 −/− mice results in more severe inflammation compared to wild type mice (Seifert et al , ), which could not be confirmed by others (Nathan et al , ). Although a precise reason for these disparate results is not known, it appears that the clinical severity reported by Seifert et al (approximately 0.75) was much lower than we report here.…”
Section: Discussionsupporting
confidence: 71%
“…For example, a 60HH variant of the IP-specific LMP2 gene has been correlated with altered MBP epitope generation and reduced risk of multiple sclerosis development in HLA-A*02 + Italian females 61 . However, in LMP2 knockout mice, MOG peptide-induced EAE symptoms were not significantly different compared to wild type animals 68 .…”
Section: Resultsmentioning
confidence: 73%